Effects of fixation on the preservation of peroxisomal structures for immunofluorescence studies using HepG2 cells as a model system - Schrader, Michael; Baumgart-Vogt, Eveline; Fahimi, H. Dariush (The histochemical journal, 1995)
The immunofluorescence technique has become an important tool for the investigation of peroxisomes in cell culture. We have used this method for the study of peroxisomes in the human hepatoblastoma cell line HepG2. A marked heterogeneity of peroxisomal forms was detected. Besides spherical (about 100 nm) and rod-shaped structures (about 300 nm) many elongated, undulating tubular forms (up to 5 μm) were found. Further observations indicate that the appearance of the peroxisomal forms in immunofluorescence is dependent on the fixation procedure used. Whereas the fixation with methanol-acetone (−20°C) or ethanol results in a punctate pattern with spherical particles, the use of formaldehyde/Triton X-100 fixation shows well-preserved tubules and rods. These observations may be of special importance for studies on the biogenesis of peroxisomes.
Gesehen am 14.01.2025